Removal of Toxic Cr(VI) Ions from Aqueous Solution Using Nano-Hydroxyapatite-Based Chitin and Chitosan Hybrid Composites - G.N. Kousalya; M. Rajiv Gandhi; S. Meenakshi (Adsorption Science & Technology)
In the present investigation, bio-inorganic composites composed of nano-hydroxyapatite (n-HAp) with chitin and chitosan have been prepared and used for the removal of chromium(VI) ions from aqueous solution. Such composites exhibited a higher Cr(VI) ion sorption capacity than the individual components. The sorption capacities of n-HAp, n-HAp/chitin (n-HApC) composite and n-HAp/chitosan (n-HApCs) composite were found to be 2720, 2845 and 3450 mg/kg, respectively. Batch adsorption studies were conducted to optimize various equilibrating conditions such as the contact time, pH and co-ions. The sorbents were characterized by FT-IR spectroscopy, BET and EDXA analysis. The sorption process could be fitted by both the Freundlich and Langmuir isotherm models. Standard thermodynamic parameters such as the Gibbs' free energy change, ΔG 0 , the standard enthalpy change, ΔH 0 , and the standard entropy change, ΔS 0 , were calculated in order to obtain an understanding of the nature of the sorption process. The kinetics of the reaction could be fitted by the pseudo-second-order and intra-particle diffusion models. The mechanism for Cr(VI) ion sorption onto the composites was established.